Chromium(VI)-Induced Electron Transfer in Penta-amminecobalt(III) Complexes of α-Amino Acids - Anbuselvan, C.; Sankaran, K.R. (Asian Journal of Chemistry, 2010)
The kinetics of 2,2´-bipyridinium chromate Cr(VI), oxidation of Cobalt(III) bound and unbound α-amino acids have been studied in the presence of 1.5 M HClO4 at 60ºC. The rate of Cr(VI) oxidation is susceptible to polar influences. The decrease in absorbance for cobalt(III) complex at 502 nm to the extent of 25% of its initial value and the formation of CO2 and Co(III) (25%), provide evidence for the cleavage of N—H and C—C bonds, occurring to the extent of 25% in a synchronous fashion as nearly so. The formation of glyoxylatopentaamminecobalt(III) complex (about 75%) during Cr(VI) oxidation of glycinatopentaamminecobalt( III) complex suggests cleavage of N—H and C—H bonds also to the extent of 75%.